A case report and literature review on giant tumefactive perivascular spaces - Cheng, Chang; Pan, Yiqi; Ma, Ke; Liu, Shuhan; Mai, Xiaoli (Frontiers in Neuroscience, 2025)
BackgroundPerivascular spaces (PVS) are fluid-filled cavities located in the brain that surround blood vessels. Dilated PVS (dPVS) can be discerned on MRI in healthy individuals. Extreme expansion of PVS is classified as giant tumefactive PVS (GTPVS), a rare condition with an ambiguous etiology. Although GTPVS may exert a mass effect, it should not be misidentified as a tumor or other pathological conditions.Case presentationWe report a rare case of GTPVS that was incidentally discovered during the examination of a scalp mass. The patient exhibited giant tumefactive dilation of PVS in the left cerebral hemisphere without any clinical symptoms. The MR imaging of this case showed a typical cluster cyst. Based on the location of the lesion, consider it belongs to Type II GTPVS.ConclusionThis study reports a rare GTPVS case, establishing diagnostic criteria, differential diagnosis, and management strategies. While asymptomatic cases require no treatment, hydrocephalus may necessitate surgery. Literature review suggests PVS dilation reflects glymphatic dysfunction, providing new pathophysiological insights. Further studies are needed to validate these findings due to the condition’s rarity.